Safe Drug Administration in Pediatric Nursing Education: A Quasi-Experimental Design Study - Kan Onturk, Zehra; Sanci, Yagmur (ATATURK UNIV, 2023)
Pediatric Nursing Days, Istanbul, TURKEY, APR 07-10, 2019
Keywords: Safe drug; self\\-confidence; pediatric nursing; simulation